Bentuk dan Fungsi Kategori Fatis dalam Novel Alvaska Karya Matcharay - Simaremare, Juni Agus; Sipayung, Nurliana; Butar, Briswanti Butar; Purba, Meriska (IdeBahasa, 2023)
This research aims to describe the form of phatic categories and the function of phatic categories in the novel ALVASKA by Matcharay. This research method uses quantitative literature research methods. Data collection methods and techniques use listening and note-taking techniques. The data collection technique is carried out by identifying data based on the form and function of phatic categories. Based on the results of the research and discussion, it can be concluded that the phatic category in the novel ALVASKA by Matcharay is as follows (1) the phatic category can be found in four forms, namely kok, kan, sih, deh, lah, tuh, ah, dong, you know, mah, here , and well,, yeah, come on, hey, and come on. (2) the phatic category function is contained in eight functions, namely emphasizing the feeling of rejection, emphasizing the reason, emphasizing the feeling of approval, emphasizing the invitation, just emphasizing (simple), emphasizing proof, starting a conversation, and justifying the statement.